EP 6. Chronic directional subthalamic nucleus deep brain stimulation in Parkinson's disease – A pilot study. Issue 9 (September 2016) - Reker, P.; Dembek, T.A.; Gierich, A.; Wirths, J.; Dafsari, H.S.; Barbe, M.T.; Timmermann, L.; Visser-Vandewalle, V.
Abstract : Question: This pilot study aimed to assess the therapeutic potential of chronically implanted directional DBS leads in patients with Parkinson's disease. The therapeutic effect of deep brain stimulation (DBS) in the subthalamic nucleus is frequently limited by side-effects resulting from unintended stimulation of neighboring areas. Recently available chronically implantable DBS leads capable of directional steering might overcome this problem. Methods: Randomized, double-blinded, standardized monopolar reviews were conducted in consecutive patients, about one week after implantation of a novel DBS system capable of directional stimulation. Clinical effects and side-effect thresholds were compared between unidirectional and circular DBS. After a two-day double-blind crossover phase, patients were asked to opt for either circular or unidirectional DBS. Results: Unidirectional DBS offered increased side-effect thresholds compared to circular DBS depending on stimulation direction. Highest side-effect thresholds were achieved with posteromedial or anterior stimulation in most cases. Conclusions: This pilot study provides preliminary evidence for advantages of directional DBS systems. Large cohorts with long-term follow-up are needed to confirm these results.